Two cases of renal cell cancer during immunobiologic therapy for psoriasis - Fabiana Palmieri Zarur; Luiza Ferreira Vieira d'Almeida; Monique Samy Pamplona Mafort; Paula Regazzi de Gusmão; João Carlos Regazzi Avelleira (Sociedade Brasileira de Dermatologia, 2014)
Immunobiologic therapy is indicated for severe forms of psoriasis, resistant to conventional therapy. There is growing concern about their safety profile and possible association with cancer development. This article documents two cases of renal cell cancer during treatment with biologic therapy, reviewing what is described in the literature . The risk of solid tumors as a complication of using TNF-alpha inhibitors is controversial. No conclusion can be drawn from the data in the literature, however, we believe that special attention should be given to those with known risk factors for a specific neoplasm.